2000
DOI: 10.1557/s1092578300005032
|View full text |Cite
|
Sign up to set email alerts
|

Deep level related yellow luminescence in p-type GaN grown by MBE on (0001) sapphire

Abstract: Yellow luminescence (YL) has been studied in GaN:Mg doped with Mg concentrations ranging from 1019 to 1021 cm-3 by spectral CL (T=K) and TEM and explained by suggesting that a different mechanism could be responsible for the YL in p-type GaN with respect to that acting in n-type GaN.Transitions at 2.2, 2.8, 3.27, 3.21, and 3.44 eV were found. In addition to the wurtzite phase, TEM showed a different amount of the cubic phase in the samples. Nano tubes with a density of 3×109 cm−2 were also observed by approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The YL band with a maximum at 2.2-2.3 eV is sometimes observed in Mg-doped GaN [4,[36][37][38][39]. We clearly distinguish this band from the GL2 band with a maximum at 2.35 eV studied in the current work.…”
Section: The Yl and Gl2 Bands In Mg-doped Gansupporting
confidence: 54%
See 2 more Smart Citations
“…The YL band with a maximum at 2.2-2.3 eV is sometimes observed in Mg-doped GaN [4,[36][37][38][39]. We clearly distinguish this band from the GL2 band with a maximum at 2.35 eV studied in the current work.…”
Section: The Yl and Gl2 Bands In Mg-doped Gansupporting
confidence: 54%
“…Note that the authors of Ref. [4] attributed the YL band to transitions from the deep N Ga donor to the shallow Mg Ga acceptor, although, in our opinion, the arguments of such an attribution are not convincing.…”
Section: A Nitrogen Vacancy In Ganmentioning
confidence: 64%
See 1 more Smart Citation
“…Nitrogen vacancies have low formation energies in p-type GaN, and they have been suggested [24] as a cause of the YL in p-GaN observed in Ref. [25]. The calculated luminescence lineshape for the transition…”
mentioning
confidence: 76%
“…12−14 In addition, the observation of YL in heavily Mg-doped p-type GaN indicated that the radiative transition between the deep donor and the Mg Ga shallow acceptor could be another possible mechanism causing YL. 15 Temperature dependence of YL intensity usually shows a normal thermal quenching behavior with a high characteristic temperature (over which YL intensity decreases rapidly) of around 450 K, caused by the thermal emission of holes from YL deep acceptors (hereafter simply denoted as YL acceptors) to the valence band. 16−19 Despite sample dependence, YL intensity was often observed to slightly attenuate from the moderate temperature in the range of 50−110 K to the room temperature in most cases.…”
Section: Introductionmentioning
confidence: 99%